Determinant Factors of Customers Loyalty in Hotels in Bandung City - Medianta Tarigan; Anastasia Wulandari; Rina Triyuningsih; Berthy Dwi Baroqah; Bela Merdianingsih (PSIKODIMENSIA, 2019)
This research verified the direct causal effects between thinking styles, customer satisfaction and service quality toward the customer loyalty. On the other hand, the indirect causal effects were verified through mediation variable such as customer satisfaction, trust, customers engagement, switching barriers, and commitment. This research used path analysis as the data analysis technique. The result revealed that service quality affected customers loyalty directly and indirectly, customers satisfaction only affected the customers loyalty if was mediated, meanwhile thinking style didn’t give significant direct and indirect effects towards customers loyalty.